Effect of local food-based supplementary feeding on the improvement of nutritional status among pregnant women with chronic energy deficiency - St. Halimatusyaadiah; Sudarmi Sudarmi; Baiq Yuni Fitri Hamidiyanti; Sumartini Sumartini (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Maternal nutritional status during pregnancy plays a critical role in ensuring optimal maternal and fetal health. Improving the nutritional status of pregnant women is essential for preventing chronic energy deficiency (CED). This study aimed to evaluate the effect of a 30-day locally sourced supplementary feeding program on the nutritional status of pregnant women at the Moyo Hilir Community Health Center in Indonesia. A pre-experimental study employing a one-group pretest–posttest design was conducted with 32 pregnant women. Nutritional status indicators were assessed before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. The results demonstrated that the locally sourced supplementary feeding program significantly improved nutritional status indicators and hemoglobin levels among pregnant women following the intervention (p = 0.001). The mean body weight increased from 47.70 ± 6.55 kg to 49.53 ± 6.73 kg. The mean mid-upper arm circumference (MUAC) increased from 21.03 ± 0.67 cm to 23.11 ± 0.75 cm. The mean body mass index (BMI) increased from 19.57 ± 2.29 kg/m² to 21.15 ± 2.57 kg/m². Furthermore, the mean hemoglobin concentration increased from 10.67 ± 1.43 g/dL to 14.48 ± 19.47 g/dL following the intervention. In conclusion, the findings indicate that locally sourced supplementary food effectively improves the nutritional status of pregnant women with chronic energy deficiency.